Trends of Antibiotic Use and Expenditure After an Intensified Antimicrobial Stewardship Policy at a 2,200-Bed Teaching Hospital in China - Qian, Xiaodan; Pan, Yuyan; Su, Dan; Gong, Jinhong; Xu, Shan; Lin, Ying; Li, Xin (Frontiers in Public Health, 2021)
Objective: This study aimed to evaluate the effects of intensified Chinese special rectification activity on clinical antibiotic use (CSRA) policy on a tertiary-care teaching hospital. Methods: A 48-month longitudinal dataset involving inpatients, outpatients, and emergency patients were collected. Study period included pre-intervention stage (adopting soft measures like systemic training) and post-intervention stage (applying antibiotic control system to intensify CSRA policy). Antibiotic use was evaluated by antibiotic use rate (AUR) or antibiotic use density (AUD). Economic indicator was evaluated by antibiotic cost in prescription or antibiotic expenditure in hospitalization. Data was analyzed by interrupted time series (ITS) analysis. Results: The medical quality indicators remained stable or improved during the study period. AUR of inpatients (AURI) declined 0.553% per month (P = 0.025) before the intervention and declined 0.354% per month (P = 0.471) after the intensified CSRA policy was implemented. AUD, expressed as defined daily doses per 100 patients per day (DDDs/100PD), decreased by 1.102 DDDs/100PD per month (P = 0.021) before and decreased by 0.597 DDDs/100PD per month (P = 0.323) thereafter. The ratio of antibiotic expenditure to medication expenditure (AE/ME) decreased by 0.510% per month (P = 0.000) before and fell by 0.096% (P = 0.000) per month thereafter. AE per patient decreased by 25.309 yuan per month (P = 0.002) before and decreased by 7.987 yuan per month (P = 0.053) thereafter. AUR of outpatient (AURO) decreased by 0.065% per month before (P = 0.550) and decreased by 0.066% per month (P = 0.994) thereafter. The ratio of antibiotic cost to prescription cost in outpatient (ACO/PCO) decreased by 0.182% per month (P = 0.506) before and decreased by 0.216% per month (P = 0.906) thereafter. AUR of emergency patient (AURE) decreased by 0.400% per month (P = 0.044) before and decreased by 0.092% per month (P = 0.164) thereafter. The ratio of antibiotic cost to prescription cost in emergency patient (ACE/PCE) decreased by 0.616% per month (P < 0.001) before and decreased by 0.151% per month (P < 0.001) thereafter. Conclusions: Implementation of CSRA policy was associated with declining antibiotic use and antibiotic expenditure in inpatients, outpatients, and emergency patients. However, it is also important to note that the declining trend of antibiotic consumption slowed due to the limited capacity for decline in the later stages of CSRA intervention.